2020
DOI: 10.1002/cnm.3373
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical behaviour of temporomandibular joints during opening and closing of the mouth: A 3D finite element analysis

Abstract: Temporomandibular joints (TMJs) constitute a pair of joints that connect the jawbone to the skull. TMJs are bilateral joints which work as one unit in conducting daily functions such as speaking, mastication, and other activities associated with the movement of the jaw. Issues associated with the TMJs may arise due to various factors—one such factor being the internal load on the TMJ. These issues may contribute to temporomandibular disorders (TMD). This study aims to evaluate the mandibular trajectories and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 43 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…The normal load F N was set as 5 N. In the ball-plate contact model, according to Hertzian theory, the surface contact area was determined by Young’s modulus, Poisson’s ratio, and metal ball diameter. The corresponding stress on PVA + PCL and natural disc of 5 N could be calculated as 1 to 2 MPa (Zimmerman et al 2015; Cao et al 2017), which was probably in the normal range of stress, according to a series of finite element analysis (Commisso et al 2014; Li et al 2014; Shu et al 2020). Last, goat serum was added to the surface of the samples because surface drying had a significant impact on the accuracy of the friction test.…”
Section: Discussionmentioning
confidence: 99%
“…The normal load F N was set as 5 N. In the ball-plate contact model, according to Hertzian theory, the surface contact area was determined by Young’s modulus, Poisson’s ratio, and metal ball diameter. The corresponding stress on PVA + PCL and natural disc of 5 N could be calculated as 1 to 2 MPa (Zimmerman et al 2015; Cao et al 2017), which was probably in the normal range of stress, according to a series of finite element analysis (Commisso et al 2014; Li et al 2014; Shu et al 2020). Last, goat serum was added to the surface of the samples because surface drying had a significant impact on the accuracy of the friction test.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the biomechanical behavior of the TMJ is considered to be influenced by the head posture [47]. Inoue et al studied the relationship between TMJ DD diagnosed by MRI and muscle pain patterns and showed that DD is possibly associated with ipsilateral muscle soreness [48].…”
Section: Discussionmentioning
confidence: 99%
“…When the condyle moved beyond the anterior hypertrophic part of the disc, high squeezing has resulted in the clicking of joints. 33,34 Additionally, the more deviated distance patients had, the greater stress would show on the non-deviated disc. And the correction should be operated as the asymmetry find.…”
Section: Discussionmentioning
confidence: 99%